Elevated blood pressure-associated cardiometabolic risk factors and biomarkers in 16–23 years old students with or without metabolic abnormalities - Šebeková, Katarína; Gurecká, Radana; Csongová, Melinda; Koborová, Ivana; Šebek, Jozef (Journal of human hypertension, 2021)
In obesity, cardiometabolic risk markers show worsening trends with increasing blood pressure (BP). We assumed that risk markers show similar trends across BP categories (normotension, high normal BP, hypertension) in metabolic abnormalities-free subjects (without obesity, insulin resistance, atherogenic dyslipidemia, hyperuricemia, microinflammation) and those presenting them. Data from 2547 (48.1% males) subjects aged 16–23 years were analyzed. The prevalence of males increased across BP categories. Forty-seven percent of individuals with elevated BP were metabolic abnormalities-free. Among 1461 metabolic abnormalities-free subjects, 9% had high normal BP, and 4% hypertension; among 1086 individuals presenting metabolic abnormalities, the prevalence reached 13% and 6%, respectively, ( p < 0.001). Both groups displayed similar BP values in corresponding BP categories and significant trends in markers of adiposity, insulin resistance, HDL-cholesterol, atherogenic index of plasma, uric acid, adiponectinemia, and antioxidant capacity of plasma across BP categories. In metabolic abnormalities-free individuals, also significant trends in soluble receptors for advanced glycation end products were revealed. Continuous metabolic syndrome score, a measure of cardiometabolic risk, increased across BP categories regardless of presence or absence of metabolic abnormalities. Multivariate regression models selected male gender, fat-free mass, and uric acid as significant independent predictors for determining BP. Our data emphasize that having a BP outside the normal range significantly worsens risk for cardiometabolic disease in young individuals even if the thresholds for any of the risk factors are not exceeded. Longitudinal studies are needed to assess whether in patients with elevated BP the prognosis of adverse outcomes differs between those presenting and not presenting metabolic abnormalities.